Grammatical Errors in Indonesian Journal: A Case of Nursing Research Article Abstracts - Noprival, Noprival; Alfian, Alfian; Kuswoyo , Heri; Adika , Dimas; Eko Pranoto, Budi; Yelia (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
Despite the existence of many studies on the analysis of grammatical errors in writing, little scholarly work reports the errors in academic articles, especially in medical journals. To fill this empirical gap, the present study investigates grammatical errors within written English abstracts of academic articles from a nursing journal in Indonesia. In particular, it attempts to classify the errors based on a surface strategy taxonomy proposed by Dulay et al. (1982), namely misformation, omission, addition, and misordering. The method used is content analysis. The results of this study indicate that errors were found from all four classification categories. Further, we noted that the most commonly found errors were in the category of misformation followed by omission, addition, and misordering. The findings of this research are expected to serve as a reference for future scholars when avoiding errors in writing English abstracts for academic articles.